High preprocedural non-HDL cholesterol is associated with enhanced oxidative stress and monocyte activation after coronary angioplasty: possible implications in restenosis. Issue 7 (1st July 2003) - Cipollone, F; Fazia, M; Iezzi, A; Pini, B; Costantini, F; De Cesare, D; Paloscia, L; Materazzo, G; D'Annunzio, E; Bucciarelli, T; Vecchiet, J; Chiarelli, F; et al.
Abstract : Objective: To investigate whether enhanced oxidant stress in patients undergoing percutaneous transluminal coronary angioplasty (PTCA) is associated with a higher concentration of non-high density lipoprotein (HDL) cholesterol at baseline, and whether this contributes to the inflammatory reaction and luminal renarrowing after PTCA. Design: An ex vivo and in vitro study of 46 patients who underwent PTCA and who had repeat angiograms after six months. Blood samples were collected immediately before PTCA, and at 24 hours, 48 hours, and 15 days after. Setting: Tertiary referral centre. Subjects: 46 patients (30 male, 16 female; mean (SD) age, 62 (5) years) with stable or unstable angina who underwent elective PTCA. Main outcome measures: Continuous variable luminal loss as defined by change in minimum lumen diameter during follow up, normalised for vessel size; lag phase of low density lipoprotein to in vitro oxidation; plasma fluorescent products of lipid peroxidation (FPLP); plasma vitamin C and E; interleukin (IL) 1β secretion from unstimulated monocytes; plasma C reactive protein (CRP). Results: Restenosis occurred in 12 patients (26%). Oxidant stress after PTCA was greater (p < 0.0001 at 15 days) in the patients with restenosis and showed a significant correlation with the preprocedural concentration of non-HDL cholesterol (p < 0.001). Inflammatory reaction (as reflected by IL-1β production and CRP) and late lumen loss were linearly correlated (p < 0.001) with lag phase and FPLP throughout the study, and inversely (p < 0.05) with vitamin C and E measured at two and 15 days after PTCA. Conclusions: This study provides evidence for the critical role of cholesterol dependent oxidant stress in the pathophysiology of restenosis after PTCA. The findings raise the possibility that drugs capable of modulating oxidant status might provide a novel form of adjuvant treatment in patients with hypercholesterolaemia undergoing PTCA.